ChemInform Abstract: Enantiospecific sp2—sp3 Coupling of Secondary and Tertiary Boronic Esters. Issue 1 (January 2015) - Bonet, Amadeu; Odachowski, Marcin; Leonori, Daniele; Essafi, Stephanie; Aggarwal, Varinder K.
Abstract For the first time, a general method for coupling electron‐rich aromatic and heteroaromatic compounds with enantioenriched secondary and tertiary boronic esters is described.